Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1186/s12882-015-0219-x
|View full text |Cite
|
Sign up to set email alerts
|

Membranoproliferative glomerulonephritis recurrence after kidney transplantation: using the new classification

Abstract: BackgroundMembranoproliferative glomerulonephritis (MPGN) is an uncommon glomerular disorder that may lead to end stage renal disease (ESRD). With new understanding of the disease pathogenesis, the classical classification as MPGN types I, II, III has changed. Data on post-transplant MPGN, in particular with the newly refined classification, is limited. We present our center’s experience of MPGN after kidney transplantation using the new classification.MethodsThis is a retrospective study of 34 patients with E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 13 publications
0
43
0
1
Order By: Relevance
“…In a recent study, after the exclusion of patients with DDD, a recurrence rate of 41% has been reported [34] . Such a high recurrence rate has been confirmed by a study published in 2016, which evaluated the recurrence rate using the new classification [35] . In another study the recurrence of Ig mediated MPGN was lower (23.5%) and after a follow up of 15 years, the graft survival rate of MPGN patients was similar to those of controls affected by different diseases [36] .…”
Section: Clinical Featuresmentioning
confidence: 75%
“…In a recent study, after the exclusion of patients with DDD, a recurrence rate of 41% has been reported [34] . Such a high recurrence rate has been confirmed by a study published in 2016, which evaluated the recurrence rate using the new classification [35] . In another study the recurrence of Ig mediated MPGN was lower (23.5%) and after a follow up of 15 years, the graft survival rate of MPGN patients was similar to those of controls affected by different diseases [36] .…”
Section: Clinical Featuresmentioning
confidence: 75%
“…Membranoproliferative glomerulonephritis recurs at a high rate after kidney transplantation . Furthermore, the recurrence of MPGN leads to an increased rate of allograft failure .…”
Section: Discussionmentioning
confidence: 99%
“…77,78 In one study, of 29 patients, 12 (41%) developed a recurrence within 1 week to 14 months, of whom 5 (42% of patients with recurrence) lost their allografts. 79 In a longitudinal study of 33 patients with MPGN (all types), 21 (49%) developed electron microscopy-proven recurrence in a mean of 4.7 years, of whom 14 (67%) lost their grafts.…”
Section: Tablementioning
confidence: 99%